Development of Comic-Based Integrated Science Teaching Materials for Fifth Grade Elementary School Students - Haris, Muhammad; Akmaluddin; Putra, Mulia (Universitas Veteran Bangun Nusantara, 2024)
Incorporating engaging and effective teaching materials is essential for enhancing student learning in science education. This research aims to develop comic-based integrated science teaching materials tailored for fifth-grade students, employing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method. The research and development process follows these five stages to ensure comprehensive material creation and evaluation. The results indicate high validation scores: 96% for material, 98% for language, and 96% for media, categorizing the comics as highly suitable for educational use. Student and teacher responses further affirm this suitability, with 90% and 94% approval rates, respectively. Evaluation of student test results shows an average score of 90.36, with 90% of students meeting the criteria for excellence. This study concludes that comic-based teaching materials significantly enhance student engagement and understanding of science, contributing valuable insights into educational resource development.